2019
DOI: 10.3233/adr-180089
|View full text |Cite
|
Sign up to set email alerts
|

BACE1 Translation: At the Crossroads Between Alzheimer’s Disease Neurodegeneration and Memory Consolidation

Abstract: Human life unfolds not only in time and space, but also in the recollection and interweaving of memories. Therefore, individual human identity depends fully on a proper access to the autobiographical memory. Such access is hindered under pathological conditions such as Alzheimer’s disease, which affects millions of people worldwide. Unfortunately, no effective cure exists to prevent this disorder, the impact of which will rise alarmingly within the next decades. While Alzheimer’s disease is largely considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 310 publications
(236 reference statements)
0
3
0
Order By: Relevance
“…This is probably due to the common symptom of cocaine intake, which reduces nitric oxide (NO). Since Hri activation depends on NO binding 43 , 44 , this inhibition of Hri (Fig. 3 d) is responsible for the conditions of HI.…”
Section: Resultsmentioning
confidence: 99%
“…This is probably due to the common symptom of cocaine intake, which reduces nitric oxide (NO). Since Hri activation depends on NO binding 43 , 44 , this inhibition of Hri (Fig. 3 d) is responsible for the conditions of HI.…”
Section: Resultsmentioning
confidence: 99%
“…The sequential cleavage of APP by β-then γ-secretases gives rise to Aβ, with BACE1 (β-site APP Cleaving Enzyme 1), the β-secretase responsible for APP cleavage, considered the rate-limiting step in its synthesis. Post mortem analysis shows an upregulation of BACE1 in the AD brain [36]. Both oxidative stress and inflammation are characteristics of AD, and are known to increase BACE1 expression and activity [3739].…”
Section: Introductionmentioning
confidence: 99%
“…NFTs comprise hyperphosphorylated tau protein, and the tau protein is phosphorylated by several kinases, including glycogen synthase kinase 3b (GSK3β), forming matured and stable microtubules ( Tiwari et al, 2019 ). The production of senile plaques and hyperphosphorylated tau is triggered by different signals, wherein the recent studies have indicated several overlapping manifestations between these two ( Chauhan and Chauhan, 2006 ; Long and Holtzman, 2019 ), which also includes endoplasmic reticulum stress (ER stress) ( Salminen et al, 2009 ; Guix et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%